Review and Critique of Economic Resistance: The East Asian Experience - Seyed Hossein Mirjalili (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The ability to absorb, withstand, or recover from adverse economic shocks makes the economy more resilient. East Asian economies were hit by the Asian financial crisis in 1997. Ten years later, these economies faced a global financial crisis in 2007. This time, despite an economic downturn due to capital outflows and a sharp drop in exports, they were resilient and resistant economies against the adverse shock. The ability of East Asian economies to recover the economy was driven by a ten-year building of the resistance economy through financial reform, structural reforms, enhancing institutional quality, and regional conditions. In this paper, beyond the financial perspective, East Asia's resilient experience in dealing with the crisis has been analyzed, and the analyses of the East Asian crisis have been criticized.